In vitro reconstitution of telomeric mono-nucleosomes - Tiu, Charles Kevin Dee (2016)
Reconstitution of telomeric DNA (telo-DNA) with human histone octamer, to form telomeric nucleosomes, was often quoted as challenging given that telo-DNA does not possess a positioning sequence and is out-of-sync with the helical periodicity of DNA. In this report, I endeavor to demonstrate telomeric mono-nucleosome reconstitution in vitro with a defined-length telomeric 145-bp DNA (telo-145) and in vitro refolded human histone octamer by salt-gradient deposition – a method currently being optimized in our laboratory. To achieve this end, telo-145 and human histone hH2B were expressed and purified in large-scale, and the histone octamer was refolded. Reconstituted telomeric mono-nucleosomes were then assessed for homogeneity and purity by electrophoretic mobility shift assays and dynamic light scattering studies. These studies suggest reconstitution has occurred with little amount of unreconstituted DNA remaining. However, the telomeric mono-nucleosome formed is heterogeneous implying that reconstitution requires further fine-tuning to achieve sufficient homogeneity. The production of pure and homogenous telomeric mono-nucleosomes will pave the way for biophysical and structural studies which would enable researchers to better comprehend telomere structure.